Modeling and optimization of an industrial ammonia synthesis unit: An exergy approach. (15th October 2017) - Flórez-Orrego, Daniel; de Oliveira Junior, Silvio
Abstract: An exergy modeling and optimization of an industrial ammonia unit based on steam methane reforming (SMR) process is presented. The base-case unit produces about 1000 t NH3/day [1], as well as power and steam, with no auxiliary exergy use. Some critical operation parameters are analyzed and the base-case and optimal operating conditions of the major components are compared. Since the ammonia synthesis process is highly exothermic, higher per-pass conversions in industrial adiabatic reactors are often achieved by using various sequential catalyst beds, where a near-optimum profile of reaction rate vs temperature can be attained by regulating the inlet temperature of each bed. This is performed via internal heat recovery, either by preheating reactor feed gas or by using waste heat boilers, which results in an increase of the steam production and a smaller fuel consumption. But, although such near-optimum operation conditions may lead to higher reaction rates and, thus, lower catalyst volumes could be required, it is found that the optimal design of the ammonia loop is rather determined by the performance of each component and their interdependencies. Moreover, since the proposed objective function (exergy destruction minimization) is very sensitive to specific process variables, the convergence of the solution algorithm is sometimes hindered. The exergy destruction breakdown shows that the ammonia converter and the refrigeration system are together responsible for more than 71–82% of the total exergy destruction in the ammonia loop, which in turn varies between 25.6 and 38.8 MW for optimal and base-case operation conditions, respectively. Highlights: An exergy modeling and optimization of an industrial ammonia unit is performed. Overall exergy destruction, its distribution and potential mitigation steps are discussed. Exergy efficiency definitions for the various components and unit operations are proposed. The strong relationship between the irreversibilities and reactor performance is highlighted.